Evaluating Consistency Across Beginner and Intermediate Filipino Textbooks for a Model of Word Level Identification - Palma Gil, Florinda Amparo A. (The Archive; Vol 5 No 2 (2024): Regular Issue Vol. 5, No. 2, 2025)
The Filipino language is taught as a second or foreign language globally, including in Asia, North America, and Europe. In Japan, Filipino classes began in 1989, but the persistent challenge remains the lack of adequate teaching and learning materials (Laranjo, 2020). Furthermore, the author observed inconsistencies in terminology—Filipino, Tagalog, or Tagalog/Filipino—across existing reference materials. Lower-level materials are variably labeled as “basic,” “beginner,” or “elementary,” while higher-level materials are broadly categorized as “intermediate.” This study aims (1) to evaluate the consistency of the language referenced in beginner and intermediate Filipino textbooks and (2) to identify differences in vocabulary between these levels, contributing to a model of word level identification, to address the following questions: (a) Are Filipino language teachers and students worldwide engaging with the same target language? (b) Are “beginner” and “intermediate” learners across countries exposed to the same vocabulary at these levels? The study compared and analyzed the glossaries of eight textbooks/reference materials used for teaching Filipino globally. Three textbooks were designated for “beginner” level, two for “intermediate,” and the remaining three for “beginner to intermediate” levels. Despite variations in how the target language is named, at least five textbooks refer to the national language of the Philippines, Filipino, as their target language. For the “beginner” level, 4,889 unique words were extracted, with 894 common across six textbooks. At the “intermediate” level, 5,767 unique words were identified, with 674 common across five textbooks. Notably, “intermediate” textbooks contained less number of nouns and verbs, but the themes under these categories were found to be more compared to those at the “beginner” level.